Iraq's road to war / edited by Amatzia Baram and Barry Rubin. - Baram, Amatzia, 1938-; Rubin, Barry M. (St. Martin's Press, 1993)
Twice in a decade, Iraq marched to war. In 1980 it invaded Iran and started an eight-year-long slaughter; and in 1990 it seized Kuwait, pitting itself against America and an international coalition. These actions propelled a little-known country into the very center of world affairs. What forces and factors set Iraq on this course? Iraq's Road to War shows how President Saddam Husayn's decision making and Iraq's domestic politics, economics, and foreign relations combined in a volatile mix. When Iran's Islamic revolution made that country seem simultaneously threatening and weak, Iraq's strong, well-armed regime seized the chance to attack its neighbor. But when fighting ended in 1988, Iraq faced economic crisis and feared social unrest. Perceiving a changing power balance - including a far weaker Iran and USSR - the regime embarked on a new effort to become the regional superpower. Finding little Arab or U.S. opposition to its escalating aggressive rhetoric, Iraq struck again to annex Kuwait and its wealth of oil. With contributions from leading experts and much new information, Iraq's Road to War provides a comprehensive picture of Iraq, its neighbors, its predicament at the end of a devastating eight-year conflict, and its decision to launch a war that shook the world.